2015
DOI: 10.5465/amj.2011.0347
|View full text |Cite
|
Sign up to set email alerts
|

Ostracism, Self-Esteem, and Job Performance: When Do We Self-Verify and When Do We Self-Enhance?

Abstract: Self-esteem level has been positioned as a key mediating mechanism accounting for the effects of ostracism on behaviors, invoking the notion that individuals seek to verify their self-perceptions by behaving consistent with those self-perceptions. However, evidence supporting the relation of ostracism and self-esteem level to behavioral outcomes has been mixed. We argue that such mixed effects arise because individuals may alternately seek to verify their self-perceptions via behavioral outcomes (suggesting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
246
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(280 citation statements)
references
References 84 publications
20
246
1
2
Order By: Relevance
“…Self-esteem levels affect employees' work skills, ability to cope with stress, ability to form relationships on the job, and level of dynamism. Several research studies, including Chang et al (2012), Ferris et al (2010), Ferris et al (2014), Judge and Bono (2001), and Sommer and Baumeister (2002), point out that increasing self-esteem improves job performance and organizational performance. Therefore, the following hypothesis was proposed: H4: Self-esteem has a significant positive effect on hotel employees' job performance.…”
Section: (Refer To Figure 1 Within Text)mentioning
confidence: 99%
“…Self-esteem levels affect employees' work skills, ability to cope with stress, ability to form relationships on the job, and level of dynamism. Several research studies, including Chang et al (2012), Ferris et al (2010), Ferris et al (2014), Judge and Bono (2001), and Sommer and Baumeister (2002), point out that increasing self-esteem improves job performance and organizational performance. Therefore, the following hypothesis was proposed: H4: Self-esteem has a significant positive effect on hotel employees' job performance.…”
Section: (Refer To Figure 1 Within Text)mentioning
confidence: 99%
“…In fact, as a universal phenomenon that exists in all types of organizations (e.g., Ferris et al, 2008), workplace ostracism has received burgeoning scholarly attention for the past decade. As a kind of negative interpersonal experience, it can bring emotional exhaustion and depression, weaken self-regulatory resources (Ferris et al, 2015;Wu et al, 2012), reduce job satisfaction, job performance and organizational citizenship behaviors, and raise deviant behaviors and turnover intention (Ferris et al, 2008;Ferris et al, 2015). Previous studies suggest that the causes of workplace exclusion can be divided into two categories: punitive tendency and protective tendency (Robinson et al, 2013).…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Workplace ostracism as a type of interpersonal mistreatment has been found to bring negative consequences on employees' attitudes toward work, such as lower job satisfaction, higher turnover intention (e.g., Ferris et al, 2008), and reduced personal well-being, such as emotional exhaustion and psychological distress (Ferris et al, 2008;Wu, Yim, Kwan, & Zhang, 2012). Because of the negative attitudinal impact, workplace ostracism can be detrimental to organizational effectiveness, as ostracized employees may reduce their engagement in citizenship behavior that can benefit others individually or the organization collectively (e.g., Ferris, Lian, Brown, & Morrison, 2015). Nevertheless, experimental studies suggest that workplace ostracism can increase employees' prosocial behavior to benefit others and the work group, for the sake of being accepted (e.g., Derfler-Rozin, Pillutla, & Thau, 2010;Williams & Sommer, 1997).…”
mentioning
confidence: 99%
“…Drawing from the self-esteem threat perspective, Ferris et al (2015) theorized and found that when ostracized, employees showed lower self-esteem and engaged less in citizenship behavior in order to be consistent with their deficient self-views. Following a resources depletion perspective, Leung, Wu, Chen, and Young (2011) reported that being ostracized depletes employees' regulatory resources and leads to a lower level of engagement at work, and thus less citizenship behavior.…”
mentioning
confidence: 99%